Explosive spalling of ultra-high performance fibre reinforced concrete beams under fire. (12th December 2016) - Kahanji, C.; Ali, F.; Nadjai, A.
Abstract : Purpose: The purpose of the study was to investigate the spalling phenomenon in ultra-high performance fibre reinforced concrete (UHPFRC) beams on exposure to a standard fire curve (ISO 834) under a sustained load. Design/methodology/approach: The variables in this study were steel fibre dosage, polypropylene (PP) fibres and loading levels. The research investigated seven beams – three of which contained steel fibres with 2 vol.%, another three had steel fibres with 4 vol.% dosage and the seventh beam had a combination of steel fibres (2 vol.%) and PP fibres (4 kg/m 3 ). The beams were tested for 1 h under three loading levels (20, 40 and 60 per cent) based on the ambient temperature ultimate flexural strength of the beam. Findings: Spalling was affected by the loading levels; it exacerbated under the load level of 40 per cent, whereas under the 60 per cent load level, significantly less spalling was recorded. Under similar loading conditions, the beams containing steel fibres with a dosage of 4 vol.% spalled less than the beams with fibre contents of 2 vol.%. This was attributed to the additional tensile strength provided by the excess steel fibres. The presence of PP fibres eliminated spalling completely. Originality/value: There is insufficient research into the performance of UHPFRC beams at elevated temperature, as most studies have largely focussed on columns, slabs and smaller elements such as cubes and cylinders. This study provides invaluable information and insights of the influence of parameters such as steel fibre dosage, PP fibres, loading levels on the spalling behaviour and fire endurance of UHPFRC beams.